Indonesian provincial clustering using Elbow method for the national food security during pandemic - Trimanto, Rido; Yustari, Eryka; Nafisah, Zulfatin; Carolina, Nona; Irsalinda, Nursyiva; Setyorini, Arifah Indah (Bulletin of Applied Mathematics and Mathematics Education, 2022)
The Covid-19 pandemic had an impact on the joints of socio-economic life, especially in fulfilling the basic needs. It also caused the declining of global food security, especially in Indonesia. This study aims to develop regional mapping to determine food security priorities and to achieve equal distribution of food security throughout Indonesia. The research method used in this research is quantitative research with the Elbow method. The Elbow method is used to find the optimal cluster size. The data used are from the Food Security Agency of the Indonesian Ministry of Agriculture and Central Statistics Agency in a range of 2020 to 2021. In the process to identify priority areas in Indonesia, it is necessary to have provincial clustering. It is also necessary to minimize food budget allocations that are not well-targeted, causing losses, and not achieving an equal distribution of food security programs. Looking from a more visionary perspective, the success of clustering provides an opportunity for the government to focus more on allocating budget, resources, and time according to the results of the clustering. Based on the results of the provincial clustering, two clusters were obtained, namely provinces with high food security (Cluster 1) and low food security (Cluster 2). Cluster 1 has lower constituent components than Cluster 2.